Efectos psicológicos en la familia como consecuencia del cuidado a personas con discapacidad física e intelectual. - Granizo Granizo, Natasha Lissette (2024)
The present research project is based on a literature review whose main objective is to systematize the relationship between the psychological effects on the family of caring for people with physical and intellectual disabilities. This research has a descriptive approach. The study began with a background search in various sources of information, selecting a total of 45 scientific documents, mainly articles in English and Spanish, using inclusion, exclusion and methodological quality criteria (CRF-QS), which allowed the selection of relevant studies that will support the current research. The results show within the sociodemographic factors that the predominance of gender in caregiving is female, while age had an approximate range of 25 to 60 years, most of them did not finish their studies, in addition, they do not have a job since they dedicate most of their time to caregiving. Among the psychological effects, there is evidence of a significant alteration in terms of the overload of care in the families, since there is no distribution of functions in relation to the care of the dependent member, there are also anxious and depressive symptoms and the presence of stress, which affects social, interpersonal and family relationships, so that they do not have support networks which generate a buffer effect of such arduous work of care.